Fictitious Capital : Silk, Cotton, and the Rise of the Arabic Novel - Holt, Elizabeth (Book collections on Project MUSE., 2017)
The ups and downs of silk, cotton and stocks synchopated with serialized novels in the late nineteenth-century Arabic press; time itself was changing. Khalil al-Khuri, Salim al-Bustani, and Jurji Zaydan wrote novels of debt, dissimulation, and risk, increasingly legible as tools of French and British empire.